Leaving violent intimate relationships: a literature review (Psicologia USP, 2021)
This article analyzes the advances and limitations in the scientific production regarding the process of leaving violent intimate relationships. For that, articles addressing leaving violent relationships or the stay/ leave process as the main theme, written in English, Portuguese, Spanish, and French, were searched in Periódicos Capes and SciELO Web searches. The search resulted in 14 articles published between 1999 and 2015 – half with a quantitative design and the other half with a qualitative design. Investment, commitment, subjective norms, responsibility attribution, anger, and structural barriers and facilitators were correlated with the leaving process. These studies also understood the end of relationship as a process. Qualitative studies proposed new models, focused on strategies that enable the leaving process, and considered the post-separation period in the analysis. Thus, this study provides recommendations for professional practice and further research on the theme.